Effectiveness of international aid for diarrheal disease control and potential for future impact - Richard A. Cash; James R. Potter (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The reduction in deaths from diarrheal diseases is one of the significant public health successes of the twentieth century. That said, the disease still accounts for a significant burden of childhood morbidity and mortality in low- and middle-income countries. Progress made in the past has, to a significant extent, been supported by a variety of both bilateral and multilateral donors aiming to make an impact in reducing this burden. We review the history of international aid in the context of disease control, and the variety of ways in which international aid has driven the international agenda, including a description of the activities of key players during this period, as well as the experiences of national control programmes. We conclude with a discussion of what is known to date about the effectiveness of international aid in supporting national control programmes, as well as some important areas of focus for future efforts. The control of diarrheal diseases remains an unfinished agenda in global health and international aid still stands to make an important impact in the burden.
Keywords: I18; 330; diarrheal disease; aid effectiveness; oral rehydration therapy; child mortality